Development, printability and post-curing studies of formulations of materials resistant to microbial attachment for use in inkjet based 3D printing - Begines, Belen; Hook, Andrew L.; Alexander, Morgan R.; Tuck, Christopher J.; Wildman, Ricky D. (Emerald, 2016)
Purpose: This paper aims to print 3D structures from polymers that resist bacterial attachment by reactive jetting of acrylate monomers. Design/methodology/approach: The first step towards printing was ink development. Inks were characterised to carry out an estimation of their potential printability using the Z parameter to predict stable jetting conditions. Printability conditions were optimised for each ink using a Dimatix DMP-2800, which enabled 3D structures to be fabricated. Findings: UV photo-initiated polymers, which resist bacterial attachment, were found to be printable using piezo-based inkjet printers. The waveform required for each ink depends on the value of the Z parameter. Once the waveform and the printability parameters were optimised, 3D objects were fabricated. Research limitations/implications: This methodology has been confirmed as an effective method to 3D print materials that have been demonstrated to be bacteria resistant. However, ink curing depends on modification of some parameters (such as photoinitiator concentration or UV exposure time) which would result in an improvement of the curing process post jetting. Social implications: The combination of inkjet based 3D printing with new materials resistant to bacterial attachment means the possibility of building customised medical devices with a high level of complexity and bespoke features can be fully realised. The scope and variability of the devices produced will exceed what can be achieved using standard fabrication methodologies and can be applied to reduce the incidence of device associated infections and to address increased morbidity, mortality and health care costs associated with nosocomial infections. Originality/value: In this paper, the novel use of materials that resist bacterial attachment has been described to build 3D structures using material jetting. Its value lies on the potential impact this methodology could produce in the biomedical device and research fields.